Cressa cretica L. growing in Egypt: Phytochemical study and potential antioxidant and hepato-protective activities - Taha S. El-Alfy, Nagwa M. Ammar, Sahar Y Al-Okbi, Maha M Salama, Hanan F. Aly, Asmaa A Amer (Journal of Applied Pharmaceutical Science, 2019)
The present research was conducted to study the phytochemical constituents of the successive extracts of aerial parts of Cressa cretica L. and their antioxidant and hepatoprotective activities. Phenolic and flavonoid contents and their respective compounds were determined in ethyl acetate and 70% ethanol extract using chromatographic and spectral analyses. Unsaponifiable matter (USM) and fatty acids were investigated in the lipoidal matter by gas chromatography–mass spectrometry analysis. In vitro 2,2-diphenyl-1-picryl-hydrazyl radical scavenging activity and safety of successive extracts were assessed. The hepatoprotective effect of the safest extracts was evaluated in CCl4 intoxicated rats. Results showed that total phenolic contents were 21.07 and 22.95 mg Gallic aid equivalent/g in ethyl acetate and 70% ethanol extract, respectively, while total flavonoid contents were 6.25 and 10.18 mg catechin equivalent/g, respectively. Catechin and chlorogenic acid were the major phenolic compounds in ethyl acetate and ethanol extract, while rutin and apigenin-7-glucoside were the predominant flavonoids, respectively. Phytol was the major compound in USM, while 14-methyl-pentadecanoic acid was the predominant fatty acid. The most promising antioxidant was 70% ethanol extract. Ethyl acetate, 70% ethanol, and petroleum ether extracts showed complete safety and produced a hepatoprotective effect; ethyl acetate and 70% ethanol extracts were superior and comparable to silymarin and even more potent concerning specific biomarkers and histopathology.
Keywords: Cressa cretica L., bioactive fractions, hepatotoxicity, antioxidant activity.